BAKTI SOSIAL DI KAMPUNG NAENA MUKTIPURA - Antje Tuasela; Rosdiana; Kevin Ali Piaggio; Ericka Sesa; Marina; Diana Andini Puspita Sari (JOURNAL OF COMMUNITY DEDICATION, 2026)
Social service activities are a form of community service aimed at increasing social awareness and improving environmental quality. Naena Muktipura Village faces various environmental problems, such as the habit of indiscriminate waste disposal. The methods used include field observation and direct environmental clean-up activities carried out by students through several stages: needs analysis, preparation, implementation, and evaluation. This activity is expected to serve as an initial step in fostering clean and healthy living behaviors as well as strengthening the value of mutual cooperation in a sustainable manner in Naena Muktipura Village. The results indicate an improvement in social service activities related to environmental cleanliness, the availability of supporting facilities such as trash bins, and basic cleaning equipment including brooms, dustpans, trash bags, and gloves to support the cleaning activities conducted by the PKM team. This activity is also expected to foster collective community awareness in maintaining environmental cleanliness on a sustainable basis.